(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of the study is to synthesize Novel Hydroxyapatite (HAP) rich in Calcium phosphate that resembles the bone. These Novel HAP are synthesized from bio-waste that is from chicken egg shells. HAP can be synthesized from chicken egg shells which is considered as a biowaste. This technique helps to protect the environment from pollution caused by biowaste.The synthesized materials shows good biocompatibility as it possesses the hydrophilicity characteristics.Materials and Methods: To synthesize the Novel Hydroxyapatite from bio-waste generated from chicken egg shells. This synthesized Novel hydroxyapatite powder will compare with chemically synthesized. Novel Hydroxyapatite powder used in conventional practice for orthopedic application.Results: The synthesized Novel Hydroxyapatite from egg shells compared with Chemically synthesized one by qualitative analysis. In which the presence of phosphate ions and calcium ions was confirmed.Conclusion: This research finds the replacement for HAP used in current bone repair. This replacement found the better choice as it is cost effect and readily synthesized from biowaste that pollutes the environment. This method indirectly helps in bioremediation.